Encyclopedia of Inorganic and Bioinorganic Chemistry 2012
DOI: 10.1002/9781119951438.eibc0128.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Materials Deposition: Metal‐Organic PrecursorsUpdate based on the original article by Charles H. Winter, Wenjun Zheng and Hani M. El‐Kaderi,Encyclopedia of Inorganic ChemistrySecond Edition, © 2005, John Wiley & Sons, Ltd.

Abstract: This review describes metal‐organic precursors for the growth of metal‐containing thin films by chemical vapor deposition (CVD)‐based methods. The major emphasis is on precursors that have been reported since 2004, which corresponds to a time of major growth in this field. Progress in the development of metal‐organic precursors is documented for the main group, lanthanide, and group 4– 11 elements. In the main group elements, there has been considerable research activity directed toward the identification of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 362 publications
0
3
0
Order By: Relevance
“…To overcome these drawbacks, organometallic precursors have drawn considerable interest for metal-organic CVD (MOCVD). Typically, these complexes include nitrogen-bound moieties such as amido, imido, hydrazido, amidinate or guanidinate ligands, 13,14 and have been used in single-source or NH 3 /H 2 co-reacting conditions to deposit WN x . Unfortunately, many of these precursors still require relatively high deposition temperature (>350…”
mentioning
confidence: 99%
“…To overcome these drawbacks, organometallic precursors have drawn considerable interest for metal-organic CVD (MOCVD). Typically, these complexes include nitrogen-bound moieties such as amido, imido, hydrazido, amidinate or guanidinate ligands, 13,14 and have been used in single-source or NH 3 /H 2 co-reacting conditions to deposit WN x . Unfortunately, many of these precursors still require relatively high deposition temperature (>350…”
mentioning
confidence: 99%
“…We published a review article on metalorganic film growth precursors that were reported between 2005 and 2012. 4 This article appeared in "Encyclopedia of Inorganic and Bioinorganic Chemistry" in December 2012.…”
Section: Summary Of the Most Important Resultsmentioning
confidence: 99%
“…The use of oxygen as a gas-reagent for the production of metallic iridium has proven itself well in the case of liquid cyclopentadienyl complexes. When using the [Ir(cod)Cp Me ] precursor, pure coatings (<1 at.% C and O) are formed already at 270 • C [29,66]; however, the growth rate is low. The application of the special system of "liquid delivery" of the precursor using a tetrahydrofuran (THF) solution allows attainment of exceptionally high growth rates (up to 70 nm/min at 350 • C) [67].…”
Section: Application Of Iridium Precursors In Mocvd Processesmentioning
confidence: 99%